Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1442-2042.2008.02170.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory response syndrome after percutaneous nephrolithotomy: An assessment of risk factors

Abstract: Objectives: To analyze the risk factors for systemic inflammatory response syndrome (SIRS) after percutaneous nephrolithotomy (PCNL) and to quantitatively predict the probability of SIRS after PCNL. Methods: Medical records on 209 patients who underwent PCNL were retrospectively analyzed. The c 2 test, the t-test and a logistic regression model were used to identify key risk factors of SIRS after PCNL. A predictive equation was then formulated to assess the risk of SIRS according to the results from the logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
49
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 14 publications
9
49
2
Order By: Relevance
“…This holds true for PCNL also. Post PCNL SIRS is commonly reported in about 20-30% of patients and has the potential to progress to severe sepsis (0-3%), which has mortality rates of 50-60% [2,3,6,7]. Thus, minimising infection-related complications is priority to maintain low morbidity rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This holds true for PCNL also. Post PCNL SIRS is commonly reported in about 20-30% of patients and has the potential to progress to severe sepsis (0-3%), which has mortality rates of 50-60% [2,3,6,7]. Thus, minimising infection-related complications is priority to maintain low morbidity rates.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative fever (not always related to infections) is one of the most common complications after PCNL and can affect upto 30% of patients. Rates of systemic inflammatory response syndrome (SIRS) can be as high as 23.4-29% and rates of sepsis range from 0 to 3% (higher in recent studies) [1,2,3]. SIRS, which includes fever, tachycardia, tachypnea and leucocytosis, is poorly understood non-infectious inflammatory response of the body to stress and has the potential to progress to multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study corroborate the hypothesis that probably a non-infectious mechanism is involved in the development of SIRS encountered after PCNL. In a previously reported study by Chen et al [11], the incidence of SIRS in 209 patients who underwent PCNL was reported as 23.4%. Number of tracts, blood transfusion, stone size and presence of pyelocaliectasis were identified as risk factors for the development of SIRS.…”
Section: Discussionmentioning
confidence: 93%
“…Positive preoperative urine culture does not predict urosepsis and systemic inflammatory response syndrome in PCNL. 26,27 Although antibiotic prophylaxis can decrease infectious complications, 28 the use of renal pelvic urine and stone cultures, and treatment of preoperative UTI should not be forgotten especially in patients with renal anomalies, hydronephrosis, large or staghorn stones and multiple tracts. 26,27 One study reported no difference in the complication rates between groups with normal and impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Although antibiotic prophylaxis can decrease infectious complications, 28 the use of renal pelvic urine and stone cultures, and treatment of preoperative UTI should not be forgotten especially in patients with renal anomalies, hydronephrosis, large or staghorn stones and multiple tracts. 26,27 One study reported no difference in the complication rates between groups with normal and impaired renal function. 29 However, another study reported that chronic kidney disease stages had significantly different complication rates and Clavien scores, and decreased kidney function came with an increase in complication rates.…”
mentioning
confidence: 99%